Improving Students` Vocabulary Mastery Through Observe and Remember Game at the Seventh Grade SMPN 2 Palopo - Helma, Helma; Jufriadi, Jufriadi (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
This thesis is about Improving Students Mastery Vocabulary Through Observe and Remember the game at the Seventh Grade SMPN 2 Palopo. The problem statement of this thesis: Is the use of Observe and Remember the game useful to improve the students’ vocabulary at the seventh grade SMPN 2 Palopo? The objective of the research: To find out whether or not the use of Observe and Remember the game is effective in improving students’ vocabulary in the seventh grade SMPN 2 Palopo. This research applied pre-experimental. The population of this research was the seventh-grade students of SMPN 2 Palopo. The population there is only one class that consists of 30 students, and the taking sample technique is a total sampling. The instrument of the research was a vocabulary test. The pre-test was given to know the basic ability of the students’ vocabulary and the post-test given to know the students’ improvement in students’ vocabulary after given the treatment and the research used to observe and remember the game. Then the test was calculated and analyzed using SPSS 20. The researcher can conclude that using Observe and Remember games is useful in improving students’ vocabulary at the seventh grade SMPN 2 Palopo. It was proven by a significant difference between the students’ mean score of pre-test and post-test. In the pre-test, the students’ mean score is 51.00, and the students’ score in the post-test is 92.33. Observe and remember the game can improve students’vocabulary because students are active in learning English. Besides, using the game can improve communication between students and teachers when learning processes. This thesis is about Improving Students Mastery Vocabulary Through Observe and Remember the game at the Seventh Grade SMPN 2 Palopo. The problem statement of this thesis: Is the use of Observe and Remember the game useful to improve the students’ vocabulary at the seventh grade SMPN 2 Palopo? The objective of the research: To find out whether or not the use of Observe and Remember the game is effective in improving students’ vocabulary in the seventh grade SMPN 2 Palopo. This research applied pre-experimental. The population of this research was the seventh-grade students of SMPN 2 Palopo. The population there is only one class that consists of 30 students, and the taking sample technique is a total sampling. The instrument of the research was a vocabulary test. The pre-test was given to know the basic ability of the students’ vocabulary and the post-test given to know the students’ improvement in students’ vocabulary after given the treatment and the research used to observe and remember the game. Then the test was calculated and analyzed using SPSS 20. The researcher can conclude that using Observe and Remember games is useful in improving students’ vocabulary at the seventh grade SMPN 2 Palopo. It was proven by a significant difference between the students’ mean score of pre-test and post-test. In the pre-test, the students’ mean score is 51.00, and the students’ score in the post-test is 92.33. Observe and remember the game can improve students’vocabulary because students are active in learning English. Besides, using the game can improve communication between students and teachers when learning processes.